PECULIARITIES OF INTERNATIONAL POSTAL DISPATCHES IN THE REPUBLIC OF MOLDOVA - Maimescu, Savva (Administrative and Criminal Justice, 2019)
In the paper the author indicates the particularities of the merchandise, objects, values, goods, money declaration, carried out by natural persons and legal entities, which are transported and placed over the customs border of the state by the specialized state carrier “Posta Moldovei”. In the paper the author indicates the subjects of declaration who have full rights to send objects, values, goods by international postal service to the recipient who has his/ her place of residence in any country. In the paper the author also indicates the liability of natural persons and legal entities, which may occur in the case of non-declaration or inauthentic declaration of merchandise, objects, values, goods sent through international postal services to the recipient, as well as reports the administrative and criminal sanctions for committing these violations.